Smoking does influence disease behaviour and impacts the need for therapy in Crohn′s disease in the biologic era. Issue 7 (26th August 2013) - Nunes, T.; Etchevers, M. J.; Domènech, E.; García‐Sánchez, V.; Ber, Y.; Peñalva, M.; Merino, O.; Nos, P.; Garcia‐Planella, E.; Casbas, A. G.; Esteve, M.; Taxonera Samsó, C.; et al.
Summary Background Recently, the notion that smoking may adversely affect Crohn′s disease (CD) outcomes has been challenged by the suggestion that the widespread use of immunosuppressants and anti‐TNF drugs might offset the adverse effects of tobacco. Aim To reassess the influence of tobacco smoking on disease phenotype and complications on a time‐dependent analysis, taking into account the different therapeutic interventions. Methods We designed a retrospective cohort study of 3224 patients with Crohn's disease. The data were collected from the Spanish national inflammatory bowel disease registry (ENEIDA), including information regarding demographics, clinical characteristics, disease complications, therapeutic interventions and smoking status. Patients were classified as nonsmokers, smokers and former smokers, according to their present and past smoking habits. Results In the univariate analysis, smokers had more strictures (22.6% vs. 19.3%, P < 0.05) and less colonic involvement (7.2% vs. 10.9%, P < 0.05), and were more frequently under treatment with steroids (91.6% vs. 85.8%, P < 0.05), immunosuppressants (73.5% vs. 63.6% P < 0.05) or anti‐TNF drugs (31.4% vs. 25.1%, P < 0.05) than nonsmokers. In the time‐dependent multivariate analysis, smokers were found to have a significantly decreased survival free of stricturing disease (HR: 1.5, CI 95% 1.18–1.90) or perianal complications (HR: 1.50, CI 95% 1.01–1.46), and had a higher risk for requiring thiopurine therapy (HR: 1.20, CI 95% 1.05–1.30). Conclusion These results suggest that, despite the widespread use of immunosuppressants and anti‐TNF drugs, smokers with Crohn's disease still have a more severe disease course, with increased therapeutic requirements when compared with nonsmokers.